Polyacrylonitrile Passivation for Enhancing the Optoelectronic Switching Performance of Halide Perovskite Memristor for Image Boolean Logic Applications - Xiaohan Zhang; Xiaoning Zhao; Zhongqiang Wang (Nanomaterials, 2023)
For the CH3NH3PbI3-based optoelectronic memristor, the high ion-migration randomness induces high fluctuation in the resistive switching (RS) parameters. Grain boundaries (GBs) are well known as the ion-migration sites due to their low energy barrier. Herein, a polyacrylonitrile (PAN) passivation method is developed to reduce GBs of the CH3NH3PbI3 film and improve the switching uniformity of the memristor. The crystal grain size of CH3NH3PbI3 increases with the addition of PAN, and the corresponding number of GBs is consequently reduced. The fluctuations of the RS parameters of the memristor device are significantly reduced. With the memristor, nonvolatile image sensing, image memory, and image Boolean operations are demonstrated. This work proposes a strategy for developing high-performance CH3NH3PbI3 optoelectronic memristors.